Effect of rootstock/scion compatibility on fruit and foliar nutrient composition in avocado (Persea americana Mill.) cv. Hass in Colombia - Tamayo-Vélez, Álvaro de Jesús; Bernal-Estrada, Jorge Alonso; Díaz-Díez, Cipriano Arturo; Cano-Gallego, Lucas Esteban; Córdoba-Gaona, Oscar de Jesús (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
There is limited information in Colombia on the effect of rootstock compatibility on the amount and concentration of nutrients in avocado cv. Hass. This study aimed to determine the effect of rootstock/scion compatibility on fruit and leaf nutritional concentration. This experiment was developed in 9-year-old commercial avocado ‘Hass’ orchards in three locations with a moderately cold climate in Colombia (Rionegro, El Peñol, and Anserma). The scion cv. Hass was grafted on rootstocks with an Antillean origin. 15 trees were selected and marked in each orchard and location, and 25 fruits per tree and per treatment were taken at random (compatible and incompatible grafting). Subsequently, the fresh and dry weight of the skin (epicarp), the pulp (mesocarp), seed, and the seedcoat were obtained. The concentration of major and minor elements was analyzed in each tissue. There was no significant effect on the concentration of nutrients in the fruits from trees with and without compatibility between rootstock and scion. Statistical differences were observed at three locations in the concentration of nutrients in the different parts of the fruit. The nutrient with the highest concentration in the four fruit tissues was K, followed by N. The seed coat had the highest concentration of nutrients for all locations. The embryo had the lowest concentration of the major elements, such as N, K, Ca, Mg, S, and P. The order of the concentration in the fruit tissues was: K> N> Mg> P> Ca> S> Fe> B> Zn > Mn. The compatibility did not show significant differences between the leaf mineral content, nor did it affect the nutrient balances for each element at the foliar level.